2005
DOI: 10.1074/jbc.m508169200
|View full text |Cite
|
Sign up to set email alerts
|

Acrolein Impairs ATP Binding Cassette Transporter A1-dependent Cholesterol Export from Cells through Site-specific Modification of Apolipoprotein A-I

Abstract: Acrolein is a highly reactive ␣,␤-unsaturated aldehyde, but the factors that control its reactions with nucleophilic groups on proteins remain poorly understood. Lipid peroxidation and threonine oxidation by myeloperoxidase are potential sources of acrolein during inflammation. Because both pathways are implicated in atherogenesis and high density lipoprotein (HDL) is anti-atherogenic, we investigated the possibility that acrolein might target the major protein of HDL, apolipoprotein A-I (apoA-I), for modifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
125
1
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 56 publications
8
125
1
3
Order By: Relevance
“…Thus, it may be anticipated that there will be more lipid-free apoE in the plasma under conditions of oxidative stress, such as aging and smoking. In a recent study, it was suggested that endogenously generated acrolein may form covalent adducts with apoAI, a related exchangeable apolipoprotein that is considered anti-atherogenic (49,50). It was noted that acrolein modification correlated with a decreased cellular cholesterol efflux capability of apoAI mediated by the ATP-binding cassette transporter AI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may be anticipated that there will be more lipid-free apoE in the plasma under conditions of oxidative stress, such as aging and smoking. In a recent study, it was suggested that endogenously generated acrolein may form covalent adducts with apoAI, a related exchangeable apolipoprotein that is considered anti-atherogenic (49,50). It was noted that acrolein modification correlated with a decreased cellular cholesterol efflux capability of apoAI mediated by the ATP-binding cassette transporter AI.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies, we noted that acrolein modified apoE3-NT without the His-tag as well (data not shown). Since N ε -(3-methylpyridinium)lysine appears to be the major epitope for mAb5F6 in other acrolein-modified proteins (48)(49)(50), it is likely that this may be the case for acrolein-modified apoE as well. The formation of other types of acrolein-lysine-adducts of apoE such as N ε -(3-formy-3,4-dehydropiperidino)lysine, for which mAb5F6 also shows some immunoreactivity (48), cannot be excluded at this point.…”
Section: Discussionmentioning
confidence: 99%
“…The acroleinlysine adducts identified include N ε -(3-formyl-3,4-dehydropiperidine)lysine (9) and N ε -(3-methylpyridinium)lysine (10). Using a specific antibody, acrolein-protein adducts have been detected immunohistochemically in Alzheimer's diseased brains (12), in the spinal cord after traumatic injury (43), and in atherosclerotic lesions (44). While covalent modifications of DNA and proteins with acrolein have been the focus of many investigations, the reaction of acrolein with glycerophosphoethanolamine lipids, another major cellular nucleophile, has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that LPO-derived RCS reacting with proteins produce such ALEs as MDA-Lys, HNE-Lys, propanal-His, propenal-Lys, and S-carboxymethyl-cysteine, as well as such cross-link as MDA-lysine dimmer, among many others ( Figure 11) (Uchida et al, 1997;Shao et al, 2005;Pamplona, 2008 and. LPO end products can also interact with amino groups of deoxyguanosine, deoxycytosine, guanosine to form various alkylated products (Pamplona, 2008).…”
Section: Advanced Lipooxidation and Glycation End Productsmentioning
confidence: 99%